2016
DOI: 10.18632/oncotarget.10252
|View full text |Cite
|
Sign up to set email alerts
|

CD147 knockdown improves the antitumor efficacy of trastuzumab in HER2-positive breast cancer cells

Abstract: Trastuzumab is widely used in the clinical treatment of human epidermal growth factor receptor-2 (HER2)-positive breast cancer, but the patient response rate is low. CD147 stimulates cancer cell proliferation, migration, metastasis and differentiation and is involved in chemoresistance in many types of cancer cells. Whether CD147 alters the effect of trastuzumab on HER2-positive breast cancer cells has not been previously reported. Our study confirmed that CD147 suppression enhances the effects of trastuzumab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 42 publications
3
22
1
Order By: Relevance
“…In a recent study, CD147 knockdown was shown to improve the antitumour efficacy of trastuzumab in HER2-positive breast cancer cells. 35 Although we found that plasma sCD147 levels were significantly higher in the HER2-positive breast cancer subtype than in luminal A, luminal B, and TNBC subtypes, plasma sCD147 had no association with expression of HER2 or oestrogen/progesterone receptors in breast cancer. The reason for this finding is that there are four breast cancer subtypes-luminal A, luminal B, HER2-positive, and TNBC-according to oestrogen/ progesterone receptor, HER2, and Ki67 status.…”
Section: Discussioncontrasting
confidence: 69%
“…In a recent study, CD147 knockdown was shown to improve the antitumour efficacy of trastuzumab in HER2-positive breast cancer cells. 35 Although we found that plasma sCD147 levels were significantly higher in the HER2-positive breast cancer subtype than in luminal A, luminal B, and TNBC subtypes, plasma sCD147 had no association with expression of HER2 or oestrogen/progesterone receptors in breast cancer. The reason for this finding is that there are four breast cancer subtypes-luminal A, luminal B, HER2-positive, and TNBC-according to oestrogen/ progesterone receptor, HER2, and Ki67 status.…”
Section: Discussioncontrasting
confidence: 69%
“…1d ) whereas HCC1954 cells were resistant (Fig. 1c ) to trastuzumab treatment in vitro , which are in agreement with published studies by other group 30 , 31 . However, trastuzumab was quite effective in inhibiting the growth of HCC1954 tumor in our xenograft model (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The unique xenograft model, HCC1954 injected into the flank of BALB/c- nu/nu mice, used in our study might be account for this discrepancy. In studies with reported trastuzumab resistance by the HCC1954 models, different strains of immune deficient host mice were used, which include nu/nu: Alpk 32 and CB17 SCID-beige 33 mice, or HCC1954 cells were injected into different location (i.e mammary fat pad) in the host mice 31 , 33 . In any event, because the efficacy of Enza in inhibiting HCC1954 cell growth in vitro and in vivo , our data suggest that Enza may be used to overcome trastuzumab resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In HCC, CD147 overexpression initiated a TGF-β signaling cascade, including Slug expression, cadherin switching, and morphological EMT changes [ 89 ]. Xiong et al [ 90 ] confirmed that CD147 suppression enhanced the effects of trastuzumab of HCC cells by up-regulating the cleavage of Caspase-3/9 and PARP, and down-regulating MAPK and Akt phosphorylation.…”
Section: Introductionmentioning
confidence: 99%